THE STUDENTS’ ABILITY IN LEARNING SPEAKING BY USING HALLO APP AS MEDIA - Samuel Nugraha Cristy; Sabrun Jamil; Abdul Halim (STKIP USMAN SAFRI KUTACANE, 2022)
The objective of this research to observe is there any significant progress of students’ ability in learning speaking by using Hallo App as media on XI IPS Plus Class at SMA Negeri 1 Kutacane in the Academic Years 2021/2022. This research was done on 01th November until 15th December 2021. The population of this research are 338 students from all XI Class. The sample was taken purposive sampling which is only choose one class.The sample are the students of XI IPS Plus Class which consist of 36 students. The research gave two tests, they are pre test and post test. The data was collected by using Rubric of Speaking which focus on Pronunciation, Grammar, Vocabulary, Fluency and Comprehension. The data was analyzed by using t-test. The minimus completeness criteria in learning English for National Senior High School at SMA Negeri 1 Kutacane is 70. It was found that the pre test average is 45 and the post test average is 76,11. The data had been calculated by using t-test, the researcher found that t observation = 26,253 by seeing the t table with df n-1 of level α = 5%, it was found that t table = 1,680. It means the t observation is bigger than t-table = 26,253 > 1,680. So the rearcher took the conclusion that the hypothesis alternative in this research is received. There is a significant progress of students’ ablitiy in learning speaking by using Hallo App as media on XI IPS Plus Class at SMA Negeri 1 Kutacane in the Academic Years 2021/2022.